THE IMPACT OF TAPIOCA IMPORT ON CASSAVA PRICES IN THE DEVELOPMENT OF TAPIOCA INDUSTRY IN INDONESIA - Luriana Taslim; Amzul Rifin (Jurnal Manajemen & Agribisnis, 2019)
Indonesian governments needed to import tapioca because Indonesia’s tapioca production was unable to meet the high domestic demand. The presence of imported tapioca made it hard for the local tapioca industry to compete. In the development of the tapioca industry, cassava price holds an important role as it is the main component in tapioca production. It is also an important element in determining cassava farmers’ income. This study aimed to analyze the impact of tapioca import policy on Indonesia’s cassava price determination and to formulate a proposal of tapioca industry development involving cassava prices. The Error Correction Model was used in this study with monthly time series data collected from January 2011 until December 2016. Results showed that the import of tapioca does not affect Indonesia’s cassava price either in the short-term or long-term. However, the price and value of imported tapioca affected Indonesia’s cassava prices. The government has to keep cassava prices low to boost tapioca industry growth. In order to keep getting a high income when the prices are low, cassava farmers need to increase their cassava production and productivity, which can be achieved through extensification and intensification programs. Keywords: tapioca industry, tapioca import, price determination, cassava, ECM